Short Communication: The diversity of intestinal parasitic helminths in children of Silvercity, Linden, Guyana - JOENITTA ARTHUR -MCKENZIE,; ABDULLAH ADIL ANSARI (Society for Indonesian Biodiversity, 2018)
Arthur-McKenzie J, Ansari AA. 2018. Short Communication: The diversity of intestinal parasitic helminths in children of Silvercity, Linden, Guyana. Biodiversitas 19: 1289-1293. This study was conducted in the Silvercity area, Linden, Guyana and endeavored to determine the prevalence of intestinal parasitic helminths in children aged 5-15 and the level of awareness of these parasitic infections among community members. Questionnaires were distributed to 30 households and 26 children which accounts for 40% of the population aged 5-15 using a simple random sampling method and tested during the months of February-April 2017. The fecal samples were collected from 26 children selected randomly and were analyzed using wet mount and formalin-ether sedimentation method. The highest age was 15 and the lowest 5, the mean age was 8. The results showed that there was a 57.6% (15/26) prevalence of intestinal parasitic helminths among children aged 5-15 within the Silvercity area. Among the parasites found, Ascaris lumbricoides was the most prevalent (38%; 10/26) followed by Enterobius vermicularis (19%; 5/26), Trichuris trichiura (15%; 4/26) and hookworm (3.8%; 1/26). Study also found that the level of awareness of transmission among community members was 40%.